(untitled) (International Journal of Physiology, 2024)
Introduction : adiponectin seems to participate in the pathophysiology of comorbidities associated with obesity such as type 2 diabetes. Thus, we propose to determine the correlation of serum adiponectin to clinico-biological parameters in type 2 diabetes. Methodology : this is a case-control study with a bio-anthropometric and a biochemical examination in all participants. The arterial stiffness and the endothelial dysfunction were evaluated. Serum adiponectin and nitric oxide levels were measured by the ELISA sandwich test. Results : serum adiponectin was significantly lower in type 2 diabetic subjects (p<0.0001). In the control group, serum adiponectin was correlated positively with HDL cholesterol (r=0.279 p=0.005) and negatively with body mass index (r=-0.339 p=0.001), waist-hip ratio (r=-0.290 p=0.004), visceral fat level (r=-0.246 p=0.014), glycated hemoglobin (r=-0.215 p=0.004), insulin resistance index (r=-0.391 p<0.0001), apolipoprotein B–apolipoprotein A ratio (r=-0.226 p=0.024) and total cholesterol/HDL cholesterol (r=-0.199 p=0.047). In the diabetic group, serum adiponectin was correlated positively with HDL cholesterol (r=0.331 p=0.001) and fingers-toes pulse wave velocity (r=0.228 p=0.024), and negatively with heart rate (r=-0.224 p=0.027), reactive hyperhemic index (r=-0.364 p=0.126), total cholesterol (r=-0.212 p=0.034), and triglycerides/HDL cholesterol (r=-0.223 p=0.026). Conclusion : serum adiponectin decreases with obesity. It would protect against insulin resistance and cardiovascular dysfunction during type 2 diabetes.